The Potential of Fucoxanthin from Sargassum polycystum: Antioxidant, Antibacterial, and Photoprotective Properties - Pramesti, Rini; Setyati, Wilis Ari; Subagiyo; Anjani, Devi Oktavia (HAYATI Journal of Biosciences, 2026)
Sargassum is a genus of seaweed that is known to contain fucoxanthin. The increasing incidence of health issues related to antimicrobial resistance (AMR), free radicals, and ultraviolet (UV) radiation has prompted the exploration of natural compounds as alternative sources of pharmaceutical agents. Fucoxanthin possesses the ability to protect cells from oxidative damage and offers a wide range of health benefits. This study aimed to evaluate the potential of fucoxanthin derived from Sargassum polycystum as an antioxidant, antifungal, antibacterial, and photoprotective (sunscreen) agent. The research methods included the extraction and isolation of fucoxanthin using Open Column Chromatography (OCC), phytochemical screening, thin-layer chromatography (TLC), antibacterial and antifungal assays, antioxidant activity assessment using the DPPH method, and determination of the Sun Protection Factor (SPF). The results showed that the extract of Sargassum polycystum contains secondary metabolites such as flavonoids, alkaloids, tannins, steroids, and saponins. The fucoxanthin fraction was successfully isolated, characterized by a distinct absorption peak at 447.5 nm and a retention factor (Rf) value of 0.93. The fucoxanthin fraction showed antibacterial activity against Staphylococcus aureus, as well as antifungal activity against Trichoderma sp. and Candida albicans. The antioxidant activity of the fucoxanthin fraction was categorized as strong, with an IC50 value of 67 ppm. Its photoprotective ability was classified as maximal, with a Sun Protection Factor value of 13.71. The fucoxanthin fraction derived from Sargassum polycystum exhibits promising potential as an antibacterial, antifungal, antioxidant, and photoprotective agent, and may serve as a valuable natural resource in pharmaceutical and cosmeceutical applications.